Prostate Cancer Diagnosis, Treatment and Outcomes in Patients with Previous or Synchronous Colorectal Cancer: A Systematic Review of Published Evidence - Giuseppe Celentano; Massimiliano Creta; Luigi Napolitano; Marco Abate; Roberto La Rocca; Marco Capece; Claudia Mirone; Simone Morra; Francesco Di Bello; Luigi Cirillo; Francesco Mangiapia; Gianluigi Califano; et al. (Diagnostics, 2022)
The management of patients with prostate cancer (PCa) and previous or synchronous colorectal cancer (CRC) represents a challenging issue. A systematic review was performed in May 2022 to summarize available evidence about the diagnosis, management, and outcomes of these patients. Twenty-seven studies involving 252 patients were identified. Overall, 163 (64.7%) and 89 (35.3%) patients had synchronous and metachronous PCa and CRC, respectively. In patients with synchronous diseases, PCa treatment involved active surveillance in 1 patient, radical prostatectomy (RP) in 36 patients, radiotherapy (RT) in 60 patients, RP plus RT in 1 patient, proton beam therapy in 1 patient, and cryoablation in 1 patient. In patients with previous CRC treatment, prostate biopsy was mostly performed by transrectal approach (n = 24). The trans-perineal and suprapubic approaches were adopted in 12 and 6 cases, respectively. Surgical PCa treatment in these cases involved endoscopic extraperitoneal RP, robot-assisted RP, and not otherwise specified RP in 30, 15, and 2 cases, respectively. Biochemical recurrence rates ranged from 20% to 28%. Non-surgical PCa treatment options included brachytherapy, RT plus androgen deprivation therapy, and RT alone in 23, 2 and 4 patients, respectively. PCa specific survival was reported by one study and was 100%.